UNCONFINED GROUNDWATER FLOW PATTERN AND FACIES CHANGES AT WAY HUWI VILLAGE, SOUTH LAMPUNG - Luhut Pardamean Siringoringo; Sandi Maulana (Indonesian Institute of Sciences, 2020)
Way Huwi Village is located in South Lampung, near the Institut Teknologi Sumatera (ITERA). The purposes of this research is to know the unconfined groundwater flow pattern and groundwater facies changes. We measured the depth of water table at nine dig wells, analyzed piper diagram for groundwater facies identification. Then, we integrated groundwater flow patterns and groundwater facies from each well to analyze groundwater facies change pattern in research area. The result indicated that the unconfined groundwater flows from SW to NE of research area, following higher (SW) to lower elevation (NE). There are six patterns of unconfined groundwater facies changes: from Facies Na-Cl to Facies Na-HCO3-Cl, Facies Na-HCO3-Cl to Facies Ca-Mg-HCO3, Facies Na-HCO3-Cl to Facies Na-Cl, Facies Na-HCO3-Cl to Facies Na-SO4-Cl, Facies Ca-Mg-HCO3 to Facies Na-SO4-Cl, and Facies Ca-Mg-HCO3 to Facies Na-HCO3-Cl. ABSTRAK - Pola aliran airtanah tidak tertekan dan perubahan fasiesnya di Desa Way Huwi, Lampung Selatan. Desa Way Huwi terletak di Lampung Selatan, di dekat Institut Teknologi Sumatera (ITERA). Tujuan dari penelitian ini adalah untuk mengetahui perubahan pola aliran airtanah dan fasies airtanah yang terjadi. Kami mengukur kedalaman muka airtanah pada sembilan sumur gali, menganalisis Diagram Piper untuk mengetahui fasies airtanah. Kemudian kami mengintegrasikan pola aliran airtanah dan fasies airtanah setiap sumur untuk mengetahui pola perubahan fasies air tanah. Hasil analisa menunjukkan bahwa airtanah tidak tertekan mengalir dari Barat Daya ke Timur Laut mengikuti ketinggian yang lebih tinggi (SW) ke ketinggian yang lebih rendah (NE). Ada enam pola perubahan fasies airtanah tidak tertekan: dari Facies Na-Cl ke Facies Na-HCO3-Cl, Facies Na-HCO3-Cl ke Facies Ca-Mg-HCO3, Facies Na-HCO3-Cl ke Facies Na-Cl, Facies Na -HCO3-Cl ke Facies Na-SO4-Cl, Facies Ca-Mg-HCO3 ke Facies Na-SO4-Cl, dan Facies Ca-Mg-HCO3 ke Facies Na-HCO3-Cl